Polyaromatic hydrocarbons pollution assessment of Slovenian sea - Bajt, Oliver (Annales. Series historia naturalis, 2007)
The paper assesses pollution of the Slovenian sea in terms of polyaromatic hydrocarbons content in sediment samples and mussels. For this purpose, fluorescence spectroscopy was appliedf as a screening method.Elevated convcentrations of polyaromatic hydrocarbons were obtained in municipal harbours of the three Slovenian coastal cities...
Keywords: kemijska analiza; ogljikovodiki; onesnaževanje morja; sedimenti; slovensko morje